Classification of lands according to their capability and identification of use conflicts in a watershed - Santos, Pablo Grahl dos; Bertol, Ildegardis; Campos, Mari Lúcia; Rafaeli Neto, Sílvio Luis; Mafra, Álvaro Luiz (Revista de Ciências Agroveterinárias, 2012)
One of the first steps in the reclamation of degraded areas and consequently the conservation of the environment is to use land planning and soil management based on conservation. This procedure should be initiated by the diagnosis of natural resources in the area, primarily by the recognition of soil attributes related to its capability and use. This study aimed to determine the land capability in a watershed with 29.8 ha, in order to recommend correct soil use, based on conservation. The study was conducted in Lages, Santa Catarina, located at 27º 48' south latitude and 50º 20' west longitude, with an elevation of 916 m and climate type mesothermal humid with cool summer (Cfb). Tean soil profiles were described and soil samples were collected for mineralogical, chemical and physical analysis. Thus, we identified in the field, soil properties related to effective depth, internal drainage of the profile, slope and the type and degree of erosion, used to identify classes of land use capability. Data collection relied on the support of satellite geodesy, photogrammetry and photo interpretation. The soil and spatial data were stored and analysed using geographic information systems to generate thematic maps of the variables, indicating land capability. Taxonomically, the hydrographic unit of study presents an Alfisol, three Cambisols and two Gleysols. The land capability of the hydrographic unit varied in terms of group and class. Concerning the groups of use, were 20.89 ha A; 7.55 ha B; and 1.37 ha C. The classes of capability were 11.01 ha III, IV 7.79 ha, VI 7.61 ha, II 2.00 ha, and VIII 1.39 ha. Regarding conflict of land use, 55.6% of the total area is under rational use, while 25.69% of the area is underutilised and 18.71% is overused. Knowledge of the capability classes of land use allowed us to establish recommendations for use and management according to soil conservation principles.